A STANDARD-BASED DATA MODEL FOR CONFIGURATION MANAGEMENT AND MAINTENANCE SUPPORT - G, A, Pro. Mothey; Pro. Poulser D (International Journal of Multidisciplinary Research and Studies, 2021)
The goal of this paper is to define an information model for configuration management and maintenance, taking into consideration the full life cycle of assets. the primary step was to review the systems related to configuration management check the employment of standards and norms which are connected virtually and search for the connection of the various possible data models used for configuration management systems. A definition of the info model is presented organized in 9 layers of information and it’s applied during a use case where is checked the issues of the information model to enhance.